Profile of academic hardiness students in pharmaceutical school in Banjarmasin City - Arsyad, Muhammad; Sulistiyana, Sulistiyana; Nurrahmah, Laili Azkia (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Pharmacy school is one of the vocational schools that prepare students' vocational abilities. Students are presented with a curriculum with quite a lot of subjects so they are quite vulnerable to the emergence of potential academic stress tendencies. The possible characteristic that pharmacy students need to have is academic hardiness. This study aims to analyze or profile the academic hardiness of pharmacy students in dealing with potentially stressful academic situations. The sample of this research is the students of class XI Pharmacy school in one of the schools in Banjarmasin City. the model in this study amounted to 69 students. The instrument used in collecting data is the academic hardiness questionnaire. Data analysis used simple descriptive statistics with survey research methods. The results showed that as many as 28 or 41% of students had academic hardiness in the very high category. As many as 30 or 43% of students showed high academic hardiness, as many as 11 or 16% of students showed relatively low academic hardiness but no students showed low academic hardiness. The conclusion of this study shows that students at pharmacy school in Banjarmasin show high academic hardiness. This means that pharmacy school students in the city of Banjarmasin have high resilience which reflects their commitment, control, and challenges in carrying out academic activities even though they have quite a lot of burden in fulfilling their academic competencies.